Nurses' Moral Sensitivity Regarding the Terminally Ill - Yolima Carmona González; Amparo Montalvo Prieto (Universidad de Antioquia, 2019)
Objective. The purpose, herein, was to determine the moral sensitivity of nurses when caring for terminally ill patients. Methods. Descriptive study conducted in the city of Cartagena (Colombia) with the participation of 118 nurses with minimum experience of six months in caring for the terminally ill in general hospitalization, caring for chronic patients, and intensive care units. The study used the 23-item questionnaire on Moral Sensitivity in Nursing Care - (Sensibilidad Moral en el Cuidado Enfermero -CuSMCE-23, in spanish) - by Campillo, which has six Likert-type response options (0 = total disagreement, to 5 = total agreement) and which has two dimensions: Nurse values (12 items) and Care responses (11 items). A higher score meant a higher degree of moral sensitivity. Results. It was found that 89.8% of the participants were women; 20.3% had a graduate degree; 39.8% had less than five years of care experience; 58.5% worked in a public institution - by type of service: 58.5% worked in general hospitalization; 32.2% in the intensive care unit; and 9.3% with chronic patients. The global moral sensitivity regarding the terminally ill in the study group was at 80%. By dimensions, while the Values dimension obtained 90%, the Care responses dimension only reached 70.4%, with the latter dimension showing difficulties in the items: 'Often, when I am with a patient, I talk about myself to be more comfortable' (27.1%), 'It is hard for me to accept certain decisions by the patients' (55.1%), and 'It is hard for me to identify concerns regarding the religious expression' (60.2%). Conclusion. Although the global levels of nurse's moral sensitivity regarding the terminally ill and of the dimension Nurse Values are high, the dimension of Care responses has limitations, especially in accepting the diversity of expressions presented by patients    How to cite this article: Carmona Y, Montalvo A. Nurses' Moral Sensitivity Regarding the Terminally Ill. Invest. Educ. Enferm. 2019; 37(3):e07.